Spanish Adaptation of Meaning-Centered Psychotherapy for Participants With Cancer: Study Protocol of a Randomized Control Trial - Marco, Jose Heliodoro; Llombart, Pilar; Guillén, Verónica; Baños, Rosa M.; Romero, Rocio; Garcia-Conde, Ana; Pérez Rodríguez, Sandra (Frontiers in Psychiatry, 2022)
Background Meaning-Centered Psychotherapy (MCP) is effective in improving meaning in life, hope, optimism, self-efficacy, well-being, and quality of life, and in reducing stress in people with cancer. However, all the studies on the application of MCP in cancer patients have been carried out in Anglo-Saxon samples. Therefore, it is necessary to adapt and verify the efficacy of MCP in populations that speak languages other than English, such as Spanish. Moreover, to expand the data supporting the efficacy of MCP for cancer patients, it would be necessary to compare MCP to other active therapies such as Cognitive Behavioral Therapy (CBT). Methods The aims of the proposed study are: the first objective is to verify the efficacy of the MCP intervention for Spanish participants with cancer in a randomized control trial (RCT) comparing it to CBT. The second objective is to analyze the feasibility and acceptance of MCP in Spanish participants with cancer. The third objective is to analyze whether the changes produced in the meaning in life dimensions (presence, search, comprehension, purpose, and mattering) will predict changes in anxiety, depression, quality of life, etc. Our research team adapted MCP for Spanish participants with cancer. This paper presents the study protocol. The study design consists of a two-arm RCT with two conditions: MCP and CBT, where participants will be randomized to one of the two groups. Eligible participants will be adults with stage I, II, and III cancer who were treated with curative intent and had completed their main medical treatment (surgery, radiotherapy, or chemotherapy). Participants will be assessed at pretreatment, post-treatment, and 6-month follow-up. The intention-to-treat principle will be used when analyzing data, using mixed-effects models with full information and maximum likelihood estimation. Discussion This study will provide results that confirm the efficacy of the MCP in Spanish participants with cancer. Trial Registration ClinicalTrials.gov; https://register.clinicaltrials.gov/prs/app/template/Home.vm?uid=U0005WS9&ts=4&sid=S000BOTT&cx=bvr2ue, identifier NCT05197348